Two new species of Heliantheae (Asteraceae) from Serra do Cabral, Minas Gerais, Brazil - Bueno, Vinicius R.; Nakajima, Jimi N. (Phytotaxa, 2020)
The floristic inventory carried out for Heliantheae s.l. from Serra do Cabral, Minas Gerais, Brazil, revealed two new species: Dimerostemma scabrosum characterized by its leaves ovate and scabrous, heads solitary or in pairs, pappus 4-aristate in ray flowers and 2-aristate in disc flowers; and Wedelia tenuifolia characterized by its leaves narrow, heads solitary or in pairs, peduncle long, and involucre 4–5-seriate. Descriptions, illustrations, phenological and geographic data of these species are presented.